Spider species composition in the tree-shrub strata of riparian forests and its microhabitats in southern Brazil - Rodrigues, Everton Nei Lopes (2017)
The composition of the spider fauna of riparian forests is insufficiently known. These forests, adjacent to both aquatic and terrestrial environments, are recognised as having important ecosystem functions. We compare the composition of spider assemblages of four riparian forests in different drainage basins, along with their microhabitats (edges and forest interior), in the state of Rio Grande do Sul, southern Brazil. Sampling was carried out in the riparian forests of the following rivers: Piratini, municipality of Arroio Grande; Camaquã, municipality of Cristal; Sinos, municipality of Parobé, and Maquiné, municipality of Maquiné. Two samples per season were collected in two years, by sampling the tree-shrub strata with a beating tray, following fixed transects. There were six transects per drainage basin, two per microhabitat: grassland edge, forest interior and river edge. Overall, 42,057 spiders were sampled (juveniles: 79%; adults: 21%). Among the adults (8,851 individuals), we identified 440 species. Similarity analyses (ANOSIM) indicated that the araneofauna composition of the four drainage basins differ in their quantitative (Morisita) and qualitative (Simpson) similarity indexes. There were no differences in composition among microhabitats. The composition of the Maquiné River basin was the most distinct, possibly due to a greater influence of the Atlantic forest on it and a greater dominance of the Linyphiidae Sphecozone personata (Simon, 1894) (SIMPER analysis, contribution to dissimilarity: 12.15%). Differences in spider composition on large spatial scales most likely reflect regional variations in a number of environmental factors, and result in each area having in increased importance in terms of conservation.